Studying Association between Thyroid Disorders and Helicobacter pylori infection in Iraqi Patients - Baghdad Science Journal (مجلة بغداد للعلوم)
This study was aimed to investigate the association between thyroid disorder and Helicobacter pylori infection in 122 patients (100 females and 22 males )and for comparison, 60 healthy individuals (31females and 29 males),who had no thyroid disorder, were also included in the study. Blood samples were collected from both patients and the healthier individuals. Enzyme Linked Fluorescent Assay (ELFA) technique through using Vitek Immuno Diagnostic Assay System (VIDAS) was applied to measure levels of the thyroid hormones (tri-iodothyronine T3, tetra-iodothyroxine T4) and thyroid stimulating hormone (TSH). From the results obtained, patients were classified into three groups: 40 were considered as belonging to the controlled group (26 females and 14 males), 57 to the hypothyroidism group (52 females and 5 males) and25 belonged to hyperthyroidism group (22 females and 3 males). On the other hand, highest incidence rate of thyroidism was recorded in the age group of (30-39)yrs. 19.67% , followed by (40-49)yrs. with 24.59% and(50-59)yrs. with 18.03%. When concentration and presence of anti -Helicobacter pylori IgG antibodies in the human blood samples were detected and measured by Enzyme Linked Immuno Sorrbent Assay (ELISA) technique , the results were showed high prevalence rates of H. pylori infection were detected in the hypothyroidism patients (94.07%), while the lowest prevalence rates were recorded in the healthy individuals ( 66.7%).Statistical analysis of anti –Helicobacter pylori IgG antibodies distribution among both healthy and thyroidism patients showed that highly significant differences at p < 0.01 were found between thyroid disorders patients groups.